On The Reform of Accounting Teaching In Higher Vocational Colleges Under The Mode of Cultivating Innovative Talents - You, Xiufang (International Journal of Management and Education in Human Development, 2022)
With the continuous development of China's social economy, there are more and more small and medium-sized enterprises and institutions, and the demand for Accountants is becoming more and more urgent. At present, there is more and more financial software in accounting work, which leads to higher and higher requirements for the professional quality of Accountants in enterprises. This article analyzes the shortcomings of the traditional accounting teaching mode, as well as the specific methods of accounting teaching reform in Higher Vocational Colleges under the innovative talent training mode.